Efforts Of Islamic Religious Education Teachers In Improving The Learning Discipline Of Class IX Students In The Subject Of Islamic Religious Education In State Vocational Schools In Gerung District, West Lombok Regency - Zainuddin, Zainuddin; Habiburrahman, Muhammad (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
This study analyzes the learning discipline of students in SMKN 1 Gerung and SMKN 2 Gerung, analyzes PAI learning related to the learning discipline of students in SMKN 1 Gerung and SMKN 2 Gerung, and provides teachers with the tools to improve students' discipline. The purpose is to analyze the efforts of her studying PAI in SMKN 1 Gerung and SMKN 2 Gerung. A qualitative approach is used in this study. The result of this study is the study discipline of XI students. Although the SMKN 1 Gerung and SMKN 2 Gerung classes are very good at PAI learning, some still commit violations related to study discipline. Student discipline can be viewed from her four aspects: discipline of time, discipline of learning, discipline of attitude, and discipline of worship. From the perspective of student learning discipline, PAI learning remains suboptimal. Various forms of indiscipline still exist among 11th graders, such as arriving late to class, not doing their homework, and not paying attention to their studies. Her PAI teacher's efforts to improve students' learning discipline in SMKN 1 Gerung and her SMKN 2 Gerung encourage students to do good things starting with prayer activities in the prayer room, such as performing dhuha prayers in the community. It is important to emphasize this and get used to it. Read the short surah and surah Waqiah, be polite, and pay attention to the cleanliness of your place of worship. Keywords: Effort, Discipline, Islamic Education